Vertical and horizontal bone loss following alveolar socket preservation using bone grafts and autologous platelet concentrates vs bone grafts alone: a systematic review and meta-analysis - Shivang Davda; Rawand Shado; Ines Novo Pereira; David Madruga; Haidar Hassan (BDJ Open)
Abstract Background Socket preservation is a proactive approach that limits bone loss after tooth extraction to maintain adequate bone volume, height and width. Many methods have proven effective in achieving socket preservation, including using various bone grafts and autologous platelet concentrates (APCs). Combining these two methods may lead to improved results in socket preservation and patient outcomes. Aims To compare the combined use of APCs and bone grafts in socket preservation, with the use of bone grafts alone. Primary outcomes were radiographic vertical bone loss (VBL) and horizontal bone loss (HBL). Methods A search on Pubmed, Scopus, Embase and Google Scholar databases was conducted to identify human studies using APCs in extraction sockets between January 2014 and August 2024. The inclusion criteria involved comparative human studies ranging from evidence levels II to III (Oxford Centre for Evidence-Based Medicine Levels of Evidence). For assessing bias in the included studies, the Cochrane Risk of Bias tools were used. The Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach was used to determine the quality of evidence available. Results A total of five randomised controlled trials (RCTs) were included in the analysis. Studies included the use of platelet rich fibrin (PRF), injectable platelet rich fibrin (i-PRF), advanced platelet rich fibrin (A-PRF), advanced platelet rich fibrin plus (A-PRF+) and concentrated growth factors (CGF). The risk of bias was judged high and moderate for two out of five RCTs. The analysis revealed a combined effect size for VBL reduction, with a standardized mean difference (SMD) of −0.83 (p < 0.001; 95% confidence interval (CI) = [−1.2, −0.57]; I² = 73.13%). For HBL reduction, the combined effect size was SMD = −0.72 (p < 0.001; 95% CI = [−1.08, −0.37]; I² = 68.34%). The overall evidence quality rating for the use of APCs in combination with bone grafts to reduce VBL during socket preservation was assessed as moderate, whereas to reduce HBL it was determined to be low. Conclusion The current literature demonstrates the added benefits of APCs combined with bone grafts in alveolar socket preservation compared to bone grafts alone in reducing vertical and horizontal bone loss. However, based on the GRADE assessment, the quality of evidence was judged low-to-moderate. Further randomised clinical studies would increase the certainty of the evidence.